PENGEMBANGAN WAKAF TUNAI UNTUK KEADILAN SOSIAL Studi tentang Manajemen Wakaf Tunai di Tabung Wakaf Indonesia - Sudirman Sudirman (El-QUDWAH, 2010)
Waqf is one of the most encouraged devotion in Islam, its reward will always be given to the waqif although he or she has passed away. In historical view, the existence of waqf have supported the development of Islamic mission in the whole of the world, including Indonesia. In order to develop waqf maximally, as the mandate of law number 41/2004 about waqf, the professional waqf institution is needed. Unfortunately, there are only few institutions that are able to bring this big mandate.  However, a non-government organization, named TWI (Tabung Waqaf Indonesia) focuses on this matter.This research is aimed to find model of developing cash waqf that is done by TWI to create social justice. Beside that, it explains TWI’s method to build and maintain donor’s trust. One of the focuses of this research is opportunity and threat ness faced by TWI in developing cash waqf as a role model for cash waqf developer.